2003
DOI: 10.1097/01.ju.0000074712.09279.e3
|View full text |Cite
|
Sign up to set email alerts
|

Broad Based Tension-Free Synthetic Sling for Stress Urinary Incontinence: 5-Year Outcome

Abstract: In our experience polypropylene mesh used as a broad based tension-free sling was successful for treating all types of SUI. In our opinion technique and case selection have a bearing on outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 7 publications
0
19
0
Order By: Relevance
“…None of the patients have experienced nonhealing or erosion [15,16]. The safety and efficacy of surgeon-tailored polypropylene mesh have been proven when used as a transobturator tape [16][17][18][19]. Elgamasy and associates evaluated the traditional polypropylene mesh used in hernia repair, as a transobturator vaginal tape in 40 patients.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…None of the patients have experienced nonhealing or erosion [15,16]. The safety and efficacy of surgeon-tailored polypropylene mesh have been proven when used as a transobturator tape [16][17][18][19]. Elgamasy and associates evaluated the traditional polypropylene mesh used in hernia repair, as a transobturator vaginal tape in 40 patients.…”
Section: Discussionmentioning
confidence: 96%
“…Three patients (8 %) had recurrent SUI, while prolonged retention developed with subsequent urethrolysis required in 4 %. None of the patients have experienced nonhealing or erosion [15,16]. The safety and efficacy of surgeon-tailored polypropylene mesh have been proven when used as a transobturator tape [16][17][18][19].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Thus, presence of the vaginal wall between the mesh material and urethra is thought to possibly reduce potential erosive complications. Literature presents only one clinical study on the use of broad based sling.Polypropylene mesh and bone fixation were used,yielding a success rate of 82% [25].In our technique,however,rather than fixation on the pubic bone,fixation on rectus fascia method is used. The high success rates and low complication rates in our study where synthetic materials were used may have been due to the characteristics of the mesh material as well as the DFS technique.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, polypropylene promotes tissue ingrowth and is non-degradable; therefore, its tensile strength does not decrease over time. Of 58 patients with SUI who were treated with polypropylene slings [57], the 49 available at the 5-year follow-up had a cure rate of 81%, with no infections or erosions. A retrospective analysis [58] of 29 of our patients who underwent transvaginal sacrospinous ligament fixation for prolapse repair with polypropylene mesh revealed that only two (6.8%) had prolapse recurrence with no erosions at the 2-year follow-up.…”
Section: Our Experiencementioning
confidence: 99%